The Reasons of Students Failure in the General Secondary Exam in Ma’an Governorate from the Teachers, principals and Education Supervisors, Point of View - Murad , Odeh; Aldaseen, Khaled; Mahasneh, Omar (Jordan Journal of Educational Sciences, 2016)
The present study was conducted to identify the reasons of students’ failure in the General Secondary Exam in Ma’an Governorate from the teachers, principals and educational supervisors point of view. And to provide the solutions proposed to avoid the reasons of students failure. To achieve the objectives of the study, the researchers built two questionnaires’ the first: causes of failure (36) items, distributed on five subscales (student, teacher, curriculum, exam, and school). The second: the solutions (17) items. After verification of the psychometric properties of the tools, it has been applied to the study sample that consisted of (473) teachers and schoolmaster educational supervisors in Ma’an. Results of the study showed that the domain of the student is the first one as the leading causes of failure in the high school exam. For the proposed solutions, the results showed that "Reconsidering the foundations of success in the primary and secondary phases" came the highest average among others with a high degree of importance. The results showed that there were no statically differences in the views of the study sample on the reasons of students failure, while there were statically differences in the views of the study sample on the solutions proposed to avoid the reasons of students failure. The study suggested appropriate recommendations based on the results.